Pengembangan Media Permainan Ludo dalam Penguasaan Kosakata Bahasa Arab - Aisyah Sajidah; Hikmah Maulani (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This research focuses on developing ludo game media as a means of improving mastery of Arabic vocabulary. This research was carried out to overcome limited access to supporting media in learning Arabic. The main goal is to create ludo game-based media to improve mastery of Arabic vocabulary. The research method applied follows the steps developed by Borg and Gall, which involve processes such as gathering information, planning, developing initial product forms, primary field testing, and operational product revision. The collected data was analyzed using a qualitative approach and the results were presented in the form of descriptive analysis. This research was conducted at the Al-Kautsar DTA, Bandung, with the research subjects being children who recited the Koran at the Al-Kautsar DTA. The data collection techniques used involved observation and interviews. The results of the research show that the Ludo game media is considered appropriate and appropriate as a learning tool by the children of Al-Kautsar DTA, with their positive response indicating that the use of this media is considered very interesting and fun.